Addressing special educational needs and disability in the curriculum art - Harris, Helen (Geography teacher) (Addressing special educational needs and disability in the curriculum, 2018)
"This topical book provides practical, tried and tested strategies and resources that will support teachers in making geography lessons accessible and interesting for all pupils, including those with special needs. The author draws on a wealth of experience to share her understanding of individual needs and show how the geography teacher can reduce or remove any barriers to learning."--Provided by publisher.